The Role of Learning Models in Enhancing Scientific Literacy: A Critical Review Evaluation - Winata Tegar Saputra; Diana Rochintaniawati; Rika Rafikah Agustin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This literature review examines the impact of learning models on students' scientific literacy and provides critiques of the strengths and weaknesses of the literature. These critiques offer recommendations for future research. Additionally, this review analyzes the role of socio-scientific issues in the context of scientific literacy. To conduct this review, 27 articles from Scopus-indexed journals were critically analyzed using the keywords: (1) Socio-scientific issues in science literacy, (2) model-based learning in scientific literacy, (3) inquiry-based learning in scientific literacy, and (4) socio-scientific issues using model-based learning in science literacy. The analysis was facilitated by the Publish or Perish software. The findings of this review suggest that various inquiry learning models have a positive impact on scientific literacy across different topics and support students' learning achievement. However, it was observed that two specific types of inquiry-based learning models, namely open inquiry-based learning and independent inquiry-based learning, were not effective in improving scientific literacy. Therefore, future research should focus on alternative inquiry-based learning models that have shown promising results in improving scientific literacy. Furthermore, this review highlights that the existing literature predominantly discusses socioscientific issues within the framework of curriculum settings and does not adequately address real-life problems associated with these issues.